The classic Jewish philosophers : from Saadia through the Renaissance - Schweid, Eliezer. (Supplements to The Journal of Jewish Thought and Philosophy, 2008)
This book provides a standard reference of the major medieval Jewish philosophers, as well as an eminently readable narrative of the course of medieval Jewish philosophical thought, presented as a response to the spiritual-intellectual challenges facing Judaism in that period. The accounts of Saadia, Bahya, Halevi, Maimonides, and Crescas are among the fullest available in English. Other thinkers discussed in depth include Israeli, Ibn Gabirol, Gersonides, and Albo; the work also includes capsule summaries of Bar Hiyya, Falaquera, Albalag, Duran, Abravanel and others. All of the summaries place the philosophical thought of these important thinkers in the context of the historical challenges and religious concerns of their age. This book is also available in paperback.